Beyond the Channels: Adhesion Functions of Aquaporin 0 and Connexin 50 in Lens Development - Li, Zhen; Quan, Yumeng; Gu, Sumin; Jiang, Jean X. (Frontiers in Cell and Developmental Biology, 2022)
Lens, an avascular organ involved in light transmission, contains an internal micro-circulatory system coupling ions to fluid movement, thus providing nutrients to internal lens cells and excreting the waste. This unique system makes up for the lack of vasculature and distinctively contains membrane channels responsible for maintaining lens homeostasis and lens fiber cell survival. Aquaporins (AQP) and connexins (Cx) comprise the majority of channels in the lens microcirculation system thus are essential for lens development and transparency. Mutations of AQP and Cx result in abnormal channel function and cataract formation. Interestingly, in the last decade or so, increasing evidence has emerged suggesting that in addition to their well-established channel functions, AQP0 and Cx50 play pivotal roles through channel-independent actions in lens development and performance. Specifically, AQP0 and Cx50 have been shown to have a unique cell adhesion function that mediates lens development and lens transparency. Cell adhesion is necessary for cell migration, a critical process during lens development, which requires dynamic, precise regulation of cell-matrix and cell-cell adhesion. This review provides recent advances in basic research of cell adhesion mediated by AQP0 and Cx50.